Pengaruh Pemberian Ekstrak Etanol Daun Pucuk Merah (Syzygium myrtifolium Walp) Terhadap Gambaran Sel Hepatosit Tikus Putih Jantan Galur Sprague-Dawley - Ruslani, Nada Oktista; Susianti, Susianti; Graharti, Risti; Rudianto, Waluyo (CV. Jasa Sukses Abadi, 2025)
Syzygium myrtifolium Walp., commonly known as red shoot leaves, is an ornamental plant rich in bioactive compounds such as flavonoids, tannins, and terpenoids, which exhibit antioxidant, anticancer, and antibacterial properties. However, administration at high doses may lead to hepatotoxic effects. The liver plays a central role in drug metabolism and is the first organ exposed to toxic agents, making it highly susceptible to hepatocyte necrosis. This study aimed to evaluate the effect of ethanol extract of Syzygium myrtifolium leaves on liver histopathology in male white rats (Rattus norvegicus). This experimental study employed a post-test only control group design with three groups: control, 2000 mg/kgBW, and 5000 mg/kgBW. The extract was administered orally, and hepatocyte necrosis was assessed using a histopathological scoring system. Statistical analysis included Shapiro-Wilk, Levene’s Test, One Way ANOVA, and post hoc LSD. Histopathological examination revealed normal hepatocytes in the control group, focal necrosis in the 2000 mg/kgBW group, and extensive necrosis in the 5000 mg/kgBW group. Statistical analysis confirmed normally distributed and homogeneous data, while ANOVA indicated significant differences among groups (p=0.001). Post hoc LSD test further demonstrated significant differences between the control and treatment groups as well as between both treatment doses. In conclusion, oral administration of ethanol extract of Syzygium myrtifolium leaves induces hepatocyte necrosis in male white rats, with the severity of liver damage increasing in a dose-dependent manner.